Inhibition of Collagenase by Mycosporine-like Amino Acids from Marine Sources - Hartmann, Anja; Gostner, Johanna; Fuchs, Julian E.; Chaita, Eliza; Aligiannis, Nektarios; Skaltsounis, Leandros; Ganzera, Markus (Planta Medica, 2015)
Matrix metalloproteinases play an important role in extracellular matrix remodeling. Excessive activity of these enzymes can be induced by UV light and leads to skin damage, a process known as photoaging. In this study, we investigated the collagenase inhibition potential of mycosporine-like amino acids, compounds that have been isolated from marine organisms and are known photoprotectants against UV-A and UV-B. For this purpose, the commonly used collagenase assay was optimized and for the first time validated in terms of relationships between enzyme-substrate concentrations, temperature, incubation time, and enzyme stability. Three compounds were isolated from the marine red algae Porphyra sp. and Palmaria palmata, and evaluated for their inhibitory properties against Chlostridium histolyticum collagenase. A dose-dependent, but very moderate, inhibition was observed for all substances and IC50 values of 104.0 µM for shinorine, 105.9 µM for porphyra, and 158.9 µM for palythine were determined. Additionally, computer-aided docking models suggested that the mycosporine-like amino acids binding to the active site of the enzyme is a competitive inhibition.
Keywords: collagenase; mycosporine-like amino acids; algae; skin aging